Polypropylene (PP) reinforced with recycle polyethylene terephthalate (PET) as an alternative material for new plastic product - Mohd Khairof Fais, Abd Raop (2007)
Polypropylene is one of the composite materials that have been developed to improve of its properties by reinforced with reinforcing material. This project will study on the best ratio that give high strength of Polypropylene reinforced with recycle Polyethylene Terephthalate fiber. Polypropylene will be mixed with recycle Polyethylene Terephthalate fiber through mixer and injected using injection mold machine. Then the product will then cut according to ASTM standard and tested using tensile test equipment. Result of the -study shows that 7% volume compositions of recycle Polyethylene Terephthalate fiber give the maximum value of Ultimate Tensile Strength with value of 30.04 MPa. The study also shows that presence of recycle Polyethylene Terephthalate fiber in Polypropylene will improved 10% strength of Polypropylene. Variety of application can be used by this composite material because of the improvement in tensile properties. Also, using recycle Polyethylene Terephthalate fiber can reduce the cost of the product by industries. Besides that, using recycle Polyethylene Terephthalate as an fiber also can decrease pollution.